Advances in Closed Circuit TV Systems for the Partially Sighted - Genensky, S. M.; Rand Corp., Santa Monica, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
The Rand Corporation has been doing research on closed-circuit television systems to aid the partially sighted since 1966. The current experimental system enhances the image electronically to provide a magnified image that is brighter and has greater contrast than the object being observed. The system also incorporates an easily movable platform for the material being observed or read. Test results indicate that persons with visual acuity as low as 20/1300 are able to read printed or handwritten material with the aid of the closed-circuit television system. Systems based on this research are now commercially available and have been purchased by schools, libraries, rehabilitation agencies and private individuals. (Author/RH)
Sponsoring Agency: Social and Rehabilitation Service (DHEW), Washington, DC. Div. of Research and Demonstration Grants.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Closed Circuit Television; Large Type Materials; Partial Vision; Technological Advancement; Television; Visual Impairments